2015
DOI: 10.1002/minf.201500064
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nucleotide Binding Peptides Using Star Graph Topological Indices

Abstract: The nucleotide binding proteins are involved in many important cellular processes, such as transmission of genetic information or energy transfer and storage. Therefore, the screening of new peptides for this biological function is an important research topic. The current study proposes a mixed methodology to obtain the first classification model that is able to predict new nucleotide binding peptides, using only the amino acid sequence. Thus, the methodology uses a Star graph molecular descriptor of the pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Liu et al [33] investigated and identified proteins having nucleotide-binding activity using star graph TIs. Ali et al [34,35] and Du et al [36] studied and applied some degreebased TIs such as the first Zagreb connection index, ordinary generalized geometric-arithmetic index, general Platt index, and general sum-connectivity index to establish extremal results for alkanes.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Liu et al [33] investigated and identified proteins having nucleotide-binding activity using star graph TIs. Ali et al [34,35] and Du et al [36] studied and applied some degreebased TIs such as the first Zagreb connection index, ordinary generalized geometric-arithmetic index, general Platt index, and general sum-connectivity index to establish extremal results for alkanes.…”
Section: Journal Of Chemistrymentioning
confidence: 99%